The influence of biophilic design towards student’s learning ability in University library environment / Nur Afizah Mohd Khair - Mohd Khair, Nur Afizah (2022)
Libraries provide students with numerous resources, technology, devices, and spaces to enhance their learning experience. A sustainable environmental design library might not only enhance students' quality of life and academic performance, but also their learning abilities. Some settings, including offices, hospitals, and primary schools, have considerable study on the influence of environmental design on people's abilities, whereas urban post-secondary educational environments have limited resources. For this reason, this research examines biophilic design as a way to improve student learning ability in a university library. The study investigates the design strategies, through a simulation experiment for before and after applying biophilic design using virtual reality (VR) and wearable bio monitoring sensors were used to measure blood pressure and heart rate. Learning ability tests were administered before and after towards 8 patterns from 14 pattern of biophilic design that have been selected from three university, which have been adopted 8 pattern of biophilic design. The indoor biophilic environment was associated with a decrease in participants' blood pressure and heart rate after applying biophilic design.